2018
DOI: 10.1038/s41598-018-35509-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function Studies of Asian Corn Borer Ostrinia furnacalis Pheromone Binding Protein2

Abstract: Lepidopteran male moths have an extraordinarily sensitive olfactory system that is capable of detecting and responding to minute amounts of female-secreted pheromones over great distances. Pheromone-binding proteins (PBPs) in male antennae ferry the hydrophobic ligand across the aqueous lymph to the olfactory receptor neuron triggering the response. PBPs bind ligands at physiological pH of the lymph and release them at acidic pH near the receptor while undergoing a conformational change. In Anthereae polyphemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…However, in studies that used delipidated samples, the A-form was not completely transformed into the B-form (at most ∼50%) at neutral pH. , This is the case observed in our pH titration of delipidated LdisPBP1. In contrast with BmorPBP, ApolPBP1, AtraPBP1, and OfurPBP2, the LdisPBP1 conformation at high pH showed extensive 1 H N – 15 N peak broadening and weak peak intensities in the 15 N HSQC spectra, which prevented elucidation of the second form by NMR.…”
Section: Discussionmentioning
confidence: 95%
“…However, in studies that used delipidated samples, the A-form was not completely transformed into the B-form (at most ∼50%) at neutral pH. , This is the case observed in our pH titration of delipidated LdisPBP1. In contrast with BmorPBP, ApolPBP1, AtraPBP1, and OfurPBP2, the LdisPBP1 conformation at high pH showed extensive 1 H N – 15 N peak broadening and weak peak intensities in the 15 N HSQC spectra, which prevented elucidation of the second form by NMR.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, all residues predicted were found to be consistent in the binding to both sex pheromones, indicating that these residues may be involved in the specific recognition of sex pheromones. It has been found that some residues may affect the structure of proteins (Dong et al ., 2017 b ; Mazumder et al ., 2018). Therefore, X-ray diffraction of protein–ligand complexes (Mazumder et al ., 2018) and the mutant binding assay (Laughlin et al ., 2008; Zhang et al ., 2020 b ) could be used to further analyze the molecular mechanisms of the interaction between insect PBPs and ligands.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that some residues may affect the structure of proteins (Dong et al ., 2017 b ; Mazumder et al ., 2018). Therefore, X-ray diffraction of protein–ligand complexes (Mazumder et al ., 2018) and the mutant binding assay (Laughlin et al ., 2008; Zhang et al ., 2020 b ) could be used to further analyze the molecular mechanisms of the interaction between insect PBPs and ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic boundary conditions (PBC) were used with a constant number of particles in the system, constant pressure, and constant temperature (NPT) simulation criteria. Equilibration of the system at 1 bar pressure for 1 ns was connected using a Parrinello-Rahman Barostat in this simulation [39]. Using trajectories obtained from MD simulations Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF), and the radius of gyration (Rg), were analyzed.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%